2021
DOI: 10.7906/indecs.19.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of entrepreneurial universities: experiences and challenges in digital era (a systemic approach)

Abstract: The modern world actively discusses the challenges that will lead to the Fourth Industrial Revolution. As the specialists assume, part of the jobs will be replaced by artificial intelligence. In addition, creation of completely new jobs is expected. As for the jobs that might be maintained in future, skills upgrading will be particularly important.In such a turbulent environment of economic development, universities, and in particular entrepreneurial universities, play a significant role. We think so as these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Given the rapid changes in the business world and the accelerated development of new technologies such as AI, the Internet of Things, and blockchain, it is critical to provide frontline advisory support to digital entrepreneurs and help them improve their abilities. Universities have an important role in developing the skills of entrepreneurs during the digital revolution [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the rapid changes in the business world and the accelerated development of new technologies such as AI, the Internet of Things, and blockchain, it is critical to provide frontline advisory support to digital entrepreneurs and help them improve their abilities. Universities have an important role in developing the skills of entrepreneurs during the digital revolution [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…require providing frontline advisory to support DEs and develop their skills. Universities play a big role in fostering the capabilities of entrepreneurs during the digital revolution (Dominici and Gagnidze, 2021).…”
Section: Challenge 2: Poor Direct Guidance and Advisorymentioning
confidence: 99%
“…, 2021). Due to their relevance, below a few key factors have been identified that contribute to the efficient functioning of entrepreneurial universities, namely: the creation of an “entrepreneurial environment, entrepreneurial staff as well as entrepreneurial teaching and learning; a strong entrepreneurial vision and the presence of leaders; the need for an environment of awareness to support spin-off creation; identifying factors that determine continuous organisational success” (Dominici and Gagnidze, 2021, p. 24).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%